Analisis Penerapan Sistem Informasi Pemerintah Daerah (SIPD) pada Bidang Perbendaharaan dan Kas Daerah BPPKAD Kota Probolinggo - Izzul Muttaqin; Ulfa Adiranti; Rahayu Dewi Zakiyah (Universitas Widyatama, 2023)
This article aims to analyze the implementation of the Regional Government Information System (SIPD) policy in the Treasury and Cash Sector at BPPKAD Probolinggo City. SIPD is a system designed to manage and handle treasury and cash activities in local government agencies. This article uses the theory put forward by Van Meter and Van Horn. This research provides a better understanding of the application of SIPD in the treasury and cash sector at BPPKAD Probolinggo City. A qualitative review and descriptive literature approach is used as a method in this study. The data collection process is based on primary and secondary data from the results of literature studies, observations, interviews, documentation, which are then followed by analysis so that conclusions can be drawn from the findings of this research problem, namely the use of SIPD, the results of which are still not optimal, so BPPKAD Probolinggo City is still implementing the application effectively. parallel, namely SIMRAL and SIPD. The results of the discussion of this research are expected to be input for local governments in optimizing the use of SIPD to increase efficiency and accountability in regional financial management so that in the future this SIPD can run optimally.